2020
DOI: 10.3390/ijerph17207669
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, Knowledge, and Practices Concerning Indoor Environmental Pollution of Parents or Future Parents

Abstract: Indoor pollutants can have short- and long-term health effects, especially if exposure occurs during prenatal life or early childhood. This study describe the perceptions, knowledge, and practices of adults concerning indoor environmental pollution. Adults of 18 to 45 years of age were recruited in the department of Ille-et-Vilaine (Brittany-France) in 2019 through a stratified random draw in the waiting rooms of general practitioners (GPs) (n = 554) who completed a self-questionnaire. The 71% who had already … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…Furthermore, with a mean score of 69.19%, the population showed a good knowledge regarding household chemical pollution. Similar results were evidenced in 2020 in France by Daniel et al, where a population of 554 adults totalized a mean score of 68.19% [ 26 ]. However, other studies revealed lower levels of knowledge, as evidenced in 2020 by Muro et al in a study conducted in Nairobi County over a sample of 393 subjects, which indicated a low knowledge level on indoor air pollution with an average score of 38.5% and, previously, by Al-Khamees in 2018, in Kuwait, which demonstrated that the respondents had a low knowledge level on indoor air pollution at 41.47% [ 27 , 35 ].…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Furthermore, with a mean score of 69.19%, the population showed a good knowledge regarding household chemical pollution. Similar results were evidenced in 2020 in France by Daniel et al, where a population of 554 adults totalized a mean score of 68.19% [ 26 ]. However, other studies revealed lower levels of knowledge, as evidenced in 2020 by Muro et al in a study conducted in Nairobi County over a sample of 393 subjects, which indicated a low knowledge level on indoor air pollution with an average score of 38.5% and, previously, by Al-Khamees in 2018, in Kuwait, which demonstrated that the respondents had a low knowledge level on indoor air pollution at 41.47% [ 27 , 35 ].…”
Section: Resultssupporting
confidence: 84%
“…Those scores were slightly higher than Al-Khamees et al, which were 51.0% for men and 53.5% for women [ 27 ]. Also, Daniel et al found out that certain practices were not well followed by less than 60% of participants [ 26 ]. The reason why the results revealed high percentages of some incorrect behaviors rather than others is probably that these are actions performed repeatedly in daily life, and many of them become incorrect habits fueled by poor knowledge and understanding of household air pollution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, while almost 90% of residents in the Île-de-France region 2 believe that outdoor air pollution presents a major health risk, less than 50% believe so about indoor air pollution (Menard et al 2008) and overestimate indoor air quality (Langer et al 2017). In fact, households still show limited understanding of the different sources of indoor pollution and underestimate its associated sanitary risks (Grange et al 2012;Daniel et al 2020). For example, although burning incense and candles can release up to 10 times more PM2.5 than a cigarette, 68% of candle users and 58% of incense users stated that this practice has no effect on or even improves indoor air quality (Nicolas et al 2017;Tirler et al 2015;Stabile et al 2012;Andersen et al 2006).…”
Section: Context and Experimental Designmentioning
confidence: 99%
“…Bhullar et al (2014) find that higher perception of wood smoke risk is indeed associated with higher support for wood burning regulation in Australia and a higher likelihood of switching to alternative heating. More generally, despite an increased awareness of air pollution, the public still has a limited apprehension of the factors that influence indoor air quality and its effects on health (Boso et al 2018;Daniel et al 2020;Grange et al 2012;Hofflinger et al 2019). Therefore, finding levers to increase awareness of the risks associated with wood burning and other household polluting activities is of key environmental and public health concern.…”
Section: Introductionmentioning
confidence: 99%